Design and development of low-cost water tunnel for educational purpose - Zahari, M.; Dol, Sharul sham (2015)
The hydrodynamic behaviour of immersed body is essential in fluid dynamics study. Water tunnel is an example of facility required to provide a controlled condition for fluid flow research. The operational principle of water tunnel is quite similar to the wind tunnel but with different working fluid and higher flow-pumping capacity. Flow visualization in wind tunnel is more difficult to conduct as turbulent flows in wind dissipate quickly whilst water tunnel is more suitable for such purpose due to higher fluid viscosity and wide variety of visualization techniques can be employed. The present work focusses on the design and development of open flow water tunnel for the purpose of studying vortex-induced vibration from turbulent vortex shedding phenomenon. The water tunnel is designed to provide a steady and uniform flow speed within the test section area. Construction details are discussed for development of low-cost water tunnel for quantitative and qualitative fluid flow measurements. The water tunnel can also be used for educational purpose such as fluid dynamics class activity to provide quick access to visualization medium for better understanding of various turbulence motion learnt in class.